The Implications of the Tension Resulting from Palestinian Journalists' Coverage of the Confrontations between Palestinian Demonstrators and Israeli Occupation Soldiers on their Professional Performance - Abudheir, Farid; Mousa, Sudqi (Dirasat: Human and Social Sciences, 2023)
This study aimed at recognizing the professional consequences of the tension caused by Palestinian confrontations with the Israeli forces on the Palestinian journalist, as the study followed the descriptive and analytical approach and used the questionnaire as a tool to collect data from a sample of (90) and retrieved (55) questionnaires, which are valid for analysis. (43) A questionnaire, where the study concluded that it is clear from the results of the study that there is a statistically significant correlation at the level of significance (0.05) between the level of psychological tension and the professional performance of Palestinian journalists in covering confrontations between Palestinian demonstrators and Israeli occupation soldiers, where the correlation coefficient reached (0.4). Whereas, the level of psychological tension affects, by (13.9%), the professional performance of Palestinian journalists in covering confrontations between Palestinian demonstrators and Israeli occupation soldiers. In light of the results of the study, a set of recommendations was raised, the most prominent of which is the necessity to influence the media institutions in adhering to the principles of occupational safety (physical and psychological) for field journalists. Conducting training courses for journalists in the field of psychological safety. Moral support for journalists through a system of rewards and incentives. Organizing courses on the psychological and physical safety of journalists, and training journalists in methods of dealing with exceptional circumstances and dangerous situations.